Development of CMX001 (Brincidofovir) for the treatment of serious diseases or conditions caused by dsDNA viruses. Issue 10 (October 2014) - Florescu, Diana F; Keck, Megan A
<x xml:space="preserve">Abstract</x> CMX001 (hexadecyloxypropyl-cidofovir, Brincidofovir) is a broad spectrum, lipid conjugate of cidofovir that is converted intracellularly into the active antiviral, cidofovir diphosphate. The lipid conjugation results in oral bioavailability, higher intracellular concentrations of active drug, lower plasma concentrations of cidofovir and increased antiviral potency against dsDNA viruses.